2016
DOI: 10.1096/fasebj.30.1_supplement.717.3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Inhibition of Chac1 Leads to Dysregulation of Body Composition

Abstract: CHAC1 is a gamma‐glutamylcyclotransferase downstream of ATF4 in the Unfolded Protein Response. CHAC1 degrades glutathione, the primary, intracellular antioxidant, and decreases Notch signaling. Notch is the receptor for a well‐conserved signaling pathway that is essential for development and proper maintenance of adult tissues, such as mucle and bone. Due to the importance of glutathione and Notch, it is likely that CHAC1 is critical for cell function and development. Chac1−/− mice were generated to elucidate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Current results showed that regular exercise could signi cantly reduce "CHAC1" mRNA expression. It is an enzyme that could be upregulated in response to ER stress through "PERK/elF2α/ATF4/CHOP" signaling, Nrf2, ATF3 and P53 pathways [17]. CHAC1 is an enzyme that degrades GSH, which is an important antioxidant molecule.…”
Section: Chac1 Gclc Alox12mentioning
confidence: 99%
See 1 more Smart Citation
“…Current results showed that regular exercise could signi cantly reduce "CHAC1" mRNA expression. It is an enzyme that could be upregulated in response to ER stress through "PERK/elF2α/ATF4/CHOP" signaling, Nrf2, ATF3 and P53 pathways [17]. CHAC1 is an enzyme that degrades GSH, which is an important antioxidant molecule.…”
Section: Chac1 Gclc Alox12mentioning
confidence: 99%
“…Crawford et al (2018) stated that genetic inhibition of CHAC1 in mice leads to numerous Modi cations in body con guration, including decreased amount of muscle tissue and changes in bone growth, which shows the importance of CHAC1 in muscles and bones proper regulation. In addition, CHAC1 could be a crucial factor in the development of muscle and bone pathology in conditions such as osteoporosis, aging, and muscle wasting [17]. Glutamate-cysteine ligase (GCL) as the rst rate-limiting enzyme of GSH biosynthesis is considered as well.…”
Section: Introductionmentioning
confidence: 99%
“…CHAC1 has a structure (BtrG/γ-GCT fold) and an active site similar to γ-GCT and mediates the degradation of cellular glutathione [12]. Knockout of the CHAC1 gene resulted in embryonic lethality, suggesting that CHAC1 is an important intracellular functional regulator [13]. Overexpression of CHAC1 led to intracellular glutathione depletion and increased ROS levels, and decreased GPX4 protein levels [14].…”
mentioning
confidence: 99%